Afiliasi Politik Media dalam Framing Pemberitaan Debat Pilpres 2024 pada Asumsi.co dan Republika.co.id - Maulida, Faiz (Faculty of Da'wa and Communications Sciences, 2025)
This study aims to analyze how the 2024 Presidential Election debate news is framed in two mass media, namely Assumption.co and Republika.co.id. Both media are known to have political affiliations. The CEO and Founder of Assumption.co, Pangeran Siahaan, was involved as the Spokesperson for the National Winning Team (TPN) for the Ganjar-Mahfud pair. Meanwhile, Republika.co.id is a media under the auspices of PT Mahaka Media Tbk, which was founded by Erick Thohir, Chief of the National Winning Team (TKN) Fanta, one of the elements of the Prabowo-Gibran TKN. Using Robert N. Entman's framing analysis method, this study examines four key elements of framing: defining problems, diagnosing causes, making moral judgments, and recommending treatments. In addition, this study also applies two major dimensions from Entman, namely issue selection and highlighting certain aspects. The study's results reveal differences in how the two media frame news related to the presidential and vice presidential candidate pairs. Asumsi.co consistently frames the 2024 presidential debate by focusing on the positive image of the Ganjar Pranowo-Mahfud MD pair, highlighting their mature performance and mastery of the material, while republika.co.id is more varied, highlighting aspects of personality, physical gestures, and rhetoric, with a primary focus on the positive image of Prabowo Subianto as a firm and experienced leader, as well as additional highlights on Gibran Rakabuming Raka, while being more critical of Anies Baswedan, especially regarding political ethics. Keywords: Political affiliation, framing, mass media, presidential debate, framing analysis